Atrial Lesions in a Pedigree With PRKAG2 Cardiomyopathy: Involvement of Disrupted AMP-Activated Protein Kinase Signaling - Chen, Shaojie; Lin, Yongping; Zhu, Yue; Geng, Le; Cui, Chang; Li, Zhaomin; Liu, Hailei; Chen, Hongwu; Ju, Weizhu; Chen, Minglong (Frontiers in Cardiovascular Medicine, 2022)
PRKAG2 cardiomyopathy is a rare progressive disease characterized by increased ventricular wall thickness and preexcitation. Dysfunction of the protein 5'-AMP-activated protein kinase (AMPK) plays a decisive role in the progression of ventricular lesions. Although patients with the PRKAG2-R302Q mutation have a high incidence of atrial fibrillation (AF), the molecular mechanism contributing to the disease remains unclear. We carried out whole-genome sequencing with linkage analysis in 3 affected members of a family. Atrial samples were obtained from the proband via surgical intervention. Control atrium biopsies were obtained from patients with persistent AF. Pathological changes were analyzed using the hematoxylin and eosin (H&E), Masson, and periodic acid–Schiff (PAS) staining. The AMPK signaling pathway was investigated by Western blot. A murine atrial cardiomyocyte cell line (HL-1) was transfected with an adenovirus carrying the same mutation. We used ELISA to determine the AMPK activity in HL-1 cells overexpressing PRKAG2-R302Q. Pathological results showed a large quantity of glycogen accumulation and vacuolization in cardiomyocytes from the proband atrial tissue. Western blot analysis revealed that the AMPK activity was significantly downregulated compared with that of the controls. Furthermore, remarkable glycogen deposition and impairment of AMPK activity were reproduced in HL-1 cells overexpressing PRKAG2-R302Q. In the present study, we determined that the PRKAG2-R302Q mutation can directly impair atrial cardiomyocytes. This result demonstrated that the PRKAG2-R302Q mutation can lead to glycogen deposition and promote the growth of atrial lesions by disrupting the AMPK pathway.